The Innovative Directions in Agriculture of Kazakhstan - Abdrakhmanova , Dinar; Byamba, Purev; Maulet, Kadrinov (Asian Journal of Agriculture and Rural Development, 2014)
In this article ways of increase of competitiveness of agrarian production, on the basis of introduction of the innovative directions in agriculture are considered. For a sustainable development of agriculture the innovative policy which basis there is an increase of efficiency of use of scientific and technical achievements has defining value. Becomes obvious that without harmonious, scientifically reasonable and balanced innovative policy, the system principle of its realization it is impossible to solve a problem of increase of profitability of agricultural production with scientific, resource, organizational and information support. Innovative process is connected with creation, development and distribution of innovations. It is process within which producers of innovations for receiving profit create and advance innovations to their consumers. The organization of innovative activity for the purpose of innovation finishing to the end user accepts huge value. Activization of innovative activity is the main condition in system of the factors providing development and increase of efficiency of agrarian production in market economy.